2020
DOI: 10.1186/s12936-020-3126-y
|View full text |Cite
|
Sign up to set email alerts
|

Late clinical failure associated with cytochrome b codon 268 mutation during treatment of falciparum malaria with atovaquone–proguanil in traveller returning from Congo

Abstract: Background: The drug combination atovaquone-proguanil, is recommended for treatment of uncomplicated falciparum malaria in France. Despite high efficacy, atovaquone-proguanil treatment failures have been reported. Resistance to cycloguanil, the active metabolite of proguanil, is conferred by multiple mutations in the Plasmodium falciparum dihydrofolate reductase (pfdhfr) and resistance to atovaquone by single mutation on codon 268 of the cytochrome b gene (pfcytb). Case presentation: A 47-year-old female, nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The change in one nucleotide base in WA 10 and WA 24 influenced its protein sequence, which differed between L and S. Changes or mutations in protein sequences affect protein function [ 15 ]. A single mutation in codon 268 cytb of P. falciparum can cause resistance to atovaquone [ 16 ]. The nucleotide and protein sequences of WA 10 and WA 24 may be influenced by drug exposure targeting the mitochondrial electron transport chain (ETC).…”
Section: Discussionmentioning
confidence: 99%
“…The change in one nucleotide base in WA 10 and WA 24 influenced its protein sequence, which differed between L and S. Changes or mutations in protein sequences affect protein function [ 15 ]. A single mutation in codon 268 cytb of P. falciparum can cause resistance to atovaquone [ 16 ]. The nucleotide and protein sequences of WA 10 and WA 24 may be influenced by drug exposure targeting the mitochondrial electron transport chain (ETC).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in pfcytb of P. falciparum can induce treatment failures of atovaquone against P. falciparum by inhibiting parasite mitochondria electron transport mechanism [ 64 ]. A previous study has suggested that Y268N/S/C in pfcytb is related to resistance of atovaquone-proguanil (Malarone) in P. falciparum [ 65 ]. This mutation was not detected in P. falciparum isolates analyzed in this study, coinciding with a previous study on Myanmar P. falciparum isolates [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Previous case reports and studies have shown that resistance to atovaquone is associated with point mutations of the P. falciparum mitochondrial cytochrome b gene (Pfcytb) (most commonly Tyr268Ser) and resistance to proguanil is associated with point mutations in the P. falciparum dihydrofolate reductase gene (Pfdhfr-also relevant for antifolate resistance) such as N51I, C59R, and S108N. [6][7][8] A high rate of antifolate resistance is currently found in P. falciparum parasites across major areas of endemicity 2,7,9 ; however, the Tyr268Ser mutation in Pfcytb has been uncommonly reported in samples collected before therapy. 10,11 Interestingly, a report of results from a rodent model suggested that mutations in cytb may not be able to naturally spread within a Plasmodium population because of an associated fitness cost.…”
mentioning
confidence: 99%